High-freezing-resistance biomass concrete as well as preparation method and application thereof

By adding cod antifreeze protein to low-alkaline cement, it affects the freezing stress and crystalline form of concrete, the structural damage problem of existing concrete in extreme freeze-thaw environments is solved, and efficient freezing resistance is achieved and environmental pollution is reduced.

CN119797798APending Publication Date: 2025-04-11XINJIANG AGRI UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510015667.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-03
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

Existing concrete is prone to freeze-thaw damage in extreme freeze-thaw environments, resulting in structural damage and degradation of performance. Traditional anti-freeze methods have problems such as cracking, steel bar corrosion, sulfate corrosion and environmental pollution.

Method used

Cod antifreeze protein is added to low-alkaline cement, which affects the freezing temperature and crystallization morphology of the pore solution through hydrogen bonds formed with water/ice, reduces the freezing stress, and provides a suitable pH environment through low-alkaline cement, so that the antifreeze protein can function better.

Benefits of technology

It significantly improves the freezing resistance of concrete, reduces the freezing stress and freezing amount, and avoids environmental pollution and structural damage caused by traditional freezing methods.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119797798A_ABST
    Figure CN119797798A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of anti-freezing concrete preparation, in particular to high-anti-freezing biomass concrete as well as a preparation method and application thereof. The invention provides application of cod antifreeze protein in preparation of high-antifreeze concrete. The cod antifreeze protein is added into the preparation of the antifreeze concrete, and hydrogen bonds formed by amino acids in the cod antifreeze protein and water / ice influence the icing temperature and icing morphology of a pore solution and reduce the formation of large ice crystals, so that the ice crystal pressure is reduced, and the antifreeze capability of the concrete is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of frost-resistant concrete preparation, and in particular to a high-freeze-resistant biomass concrete and a preparation method and application thereof. Background Art

[0002] Concrete is very susceptible to freeze-thaw damage in harsh environments with severe periodic temperature cycles, causing huge economic losses. Therefore, how to prepare highly frost-resistant concrete for use in extreme freeze-thaw environments has always been a hot topic of concern in the engineering and academic communities.

[0003] Concrete is a porous material with many pores and microcracks inside. When the ambient temperature drops below freezing, the water that penetrates into the concrete begins to freeze. Since water expands by about 9% when it freezes, this volume expansion will generate huge frost heave forces inside the concrete. These frost heave forces try to push away the surrounding concrete particles, thereby generating stress inside the structure. As the freeze-thaw cycle repeats, the frost heave forces continue to act, causing microcracks to gradually appear inside the concrete. These microcracks will expand over time, eventually leading to damage to the concrete structure and degradation of its performance.

[0004] At present, the method of adding air entraining agent, antifreeze agent and reducing porosity is commonly used to prepare high frost resistance concrete. However, the addition of air entraining agent will reduce the strength of concrete, and the on-site construction cannot ensure the designed air content of concrete, resulting in reduced frost resistance. Problems such as alkali aggregate reaction, steel corrosion, sulfate erosion and environmental pollution caused by concrete antifreeze also limit the use of antifreeze. Reducing porosity helps to improve the density of concrete, while increasing the brittleness of concrete, making it more likely to crack and resulting in reduced frost resistance.

[0005] Inspired by the extreme low temperature adaptability of biological systems in nature, some biomass materials (antifreeze proteins) are widely used in industry, food and biological preservation, achieving good antifreeze effects. How to apply biomaterials to concrete materials, prepare high frost resistance concrete, and reduce economic losses is a top priority. Summary of the invention

[0006] The present invention provides a highly frost-resistant biomass concrete for use in extreme freeze-thaw environments. Antifreeze protein-cod antifreeze protein is added to low-alkalinity cement to enhance the antifreeze effect of the concrete. The added cod antifreeze protein is a biomass material, which is not easy to cause environmental pollution and is highly effective in small amounts, so as to solve the problems of concrete cracking, steel bar corrosion, sulfate erosion and environmental pollution caused by traditional antifreeze methods.

[0007] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0008] The invention provides application of cod antifreeze protein in preparing high-freeze-resistant concrete.

[0009] The present invention also provides a high-freeze-resistant biomass concrete, comprising the following components in parts by weight: 0.1 to 0.5 parts of cod antifreeze protein, 8 to 16 parts of cement and 25 to 35 parts of aggregate.

[0010] Preferably, the cement is low-alkalinity sulphoaluminate cement.

[0011] Preferably, the aggregate is coarse aggregate and / or fine aggregate.

[0012] Preferably, the particle size of the coarse aggregate is 6 to 20 mm, and the bulk density is 1650 kg / m 3 The water absorption rate in 24 hours is 0.43%.

[0013] Preferably, the particle size of the fine aggregate is 2 to 5 mm.

[0014] Preferably, the aggregate is one or more of natural crushed stone, pebbles, machine-made sand or natural sand.

[0015] The present invention also provides a method for preparing the highly frost-resistant biomass concrete, comprising the following steps:

[0016] (1) mixing cod antifreeze protein with water to obtain concrete mixing water;

[0017] (2) mixing the concrete mixing water and cement to obtain cement paste;

[0018] (3) The cement paste is mixed with aggregate to obtain high frost resistance biomass concrete.

[0019] Preferably, the mass ratio of cement to water is 1:0.3-0.6.

[0020] Preferably, the method further comprises the steps of molding, vibrating, shaping and curing the high frost resistance biomass concrete.

[0021] Preferably, the stirring time in step (1) is 8 to 16 minutes.

[0022] Preferably, the stirring time in step (2) is 20 to 40 seconds.

[0023] Preferably, the stirring time in step (3) is 4 to 6 minutes.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] The present invention adds the antifreeze protein - cod antifreeze protein to low-alkalinity cement, which can effectively reduce the freezing temperature of the pore solution and change the crystal form of the pore solution from a sharp ice cone to a soft feather, presenting a softer and looser structural feature, thereby greatly reducing the frost heave stress of the concrete and significantly reducing the amount of ice. The selected low-alkalinity cement can provide a suitable pH environment for the antifreeze protein, so that the antifreeze protein can play a better role.

[0026] The proline, alanine and glutamic acid alkyl chains of the characteristic peptide chain in the cod antifreeze protein used in the present invention can provide a hydrophobic environment ( Figure 2 ), using hydrophobic interaction to arrange water molecules in a lattice, and providing hydrogen bonds to anchor the water molecule lattice through the hydroxyl groups on alanine. The anchored water molecule lattice then matches the specific ice crystal surface to allow antifreeze proteins to bind to ice crystals. The hydration layer freezes on the ice crystal surface, and the unfrozen surface forms a non-ice binding surface. The formation of a new ice crystal layer requires crossing the gaps on the non-ice binding surface, which increases the curvature of the ice nucleus surface and the energy required for water molecules to break through the ice. The resulting surface effect lowers the freezing point, thereby causing the freezing point to drop, achieving the purpose of improving the antifreeze ability of concrete.

[0027] In addition, the amino acid analysis results of cod antifreeze protein show that its hydrophilic amino acids account for 55.52%. These hydrophilic amino acids can interact with free water molecules to form hydrogen bonds, promote the conversion of free water into bound water, hinder the displacement of ice crystals, and hinder the binding of ice crystals with water molecules at the solid-liquid interface, thereby inhibiting the recrystallization of ice. The synergistic effect of hydrophilic amino acids can reduce the formation of large ice crystals and maintain the structural stability of the peptide chain. In particular, aspartic acid and glutamic acid in the protein structure are the main contributors to hydrogen bonds. The alkyl side chains of proline and alanine residues provide a partially non-polar environment for the formation of stable hydrogen bonds between them and water molecules through hydrophobic interactions. This hydrogen bonding effect not only reduces the nucleation rate of ice crystals, but also changes the growth mode and morphology of ice crystals, making the formed ice crystals smaller.

[0028] The present invention incorporates cod antifreeze protein into low-alkali cement, and the hydrogen bonds formed between amino acids in the biomass material and water / ice affect the freezing temperature and freezing morphology of the pore solution, reduce the formation of large ice crystals, thereby reducing ice crystal pressure and improving the antifreeze ability of concrete. The addition of a small amount of biomass material has a good antifreeze effect and has the characteristics of a small amount of high efficiency. The biomass material used in the present invention is green, healthy, environmentally friendly, non-toxic, has good biocompatibility, and will not affect the environment. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.

[0030] Figure 1 :Process flow chart for making high frost-resistant biomass concrete;

[0031] Figure 2 :The mechanism of action of cod antifreeze protein;

[0032] Two characteristic peptides of cod antifreeze protein were obtained by mass spectrometry: A1 represents the structure of characteristic peptide 1 in antifreeze protein and a schematic diagram of its formation of hydrogen bonds with ice crystals to lower the freezing point, A2 is the molecular formula of characteristic peptide 1 and the type, site and strength of hydrogen bonds formed by the molecular formula; B1 represents the structure of characteristic peptide 2 in antifreeze protein and a schematic diagram of its formation of hydrogen bonds with ice crystals to lower the freezing point, B2 is the molecular formula of characteristic peptide 2 and the type, site and strength of hydrogen bonds formed;

[0033] Figure 3 : Relationship between the number of freeze-thaw cycles and mass loss rate of Example 1 and Comparative Example 1;

[0034] Figure 4 : Relationship between the number of freeze-thaw cycles and mass loss rate of Example 2 and Comparative Example 2;

[0035] Figure 5 : Freezing temperature curves of Example 1 and Comparative Example 1;

[0036] Figure 6 : Freezing temperature curves of Example 2 and Comparative Example 2;

[0037] Figure 7 : Comparative Example 1 ice crystal morphology;

[0038] Figure 8 : Example 1 ice crystal morphology;

[0039] Fig. 9 : Ice crystal morphology of Example 2. DETAILED DESCRIPTION

[0040] The invention provides application of cod antifreeze protein in preparing high-freeze-resistant concrete.

[0041] The present invention also provides a high-freeze-resistant biomass concrete, comprising the following components in parts by weight: 0.1-0.5 parts of cod antifreeze protein, 8-16 parts of cement and 25-35 parts of aggregate; preferably 0.2-0.4 parts of cod antifreeze protein, 9-15 parts of cement and 27-33 parts of aggregate; further preferably 0.3 parts of cod antifreeze protein, 10-14 parts of cement and 29-31 parts of aggregate; more preferably 0.3 parts of cod antifreeze protein, 12 parts of cement and 30 parts of aggregate.

[0042] In the present invention, the cement is low-alkalinity sulphoaluminate cement.

[0043] In the present invention, the aggregate is coarse aggregate and / or fine aggregate; preferably coarse aggregate and fine aggregate.

[0044] In the present invention, the particle size of the coarse aggregate is 6 to 20 mm, preferably 8 to 18 mm, more preferably 10 to 16 mm, and more preferably 15 mm.

[0045] In the present invention, the particle size of the fine aggregate is 2 to 5 mm, preferably 3 to 4 mm, and more preferably 4 mm.

[0046] In the present invention, the aggregate is one or more of natural crushed stone, pebbles, machine-made sand or natural sand; preferably natural sand.

[0047] The present invention also provides a method for preparing the highly frost-resistant biomass concrete, comprising the following steps:

[0048] (1) mixing cod antifreeze protein with water to obtain concrete mixing water;

[0049] (2) mixing the concrete mixing water and cement to obtain cement paste;

[0050] (3) The cement paste is mixed with aggregate to obtain high frost resistance biomass concrete.

[0051] In the present invention, the mass ratio of cement to water is 1:0.3-0.6; preferably 1:0.4-0.5; more preferably 1:0.45.

[0052] The present invention also includes the steps of molding, vibrating, shaping and curing the high frost resistance biomass concrete.

[0053] In the present invention, the stirring time in step (1) is 8 to 16 minutes, preferably 9 to 15 minutes, more preferably 10 to 14 minutes, and more preferably 12 minutes.

[0054] In the present invention, the stirring time in step (2) is 20 to 40 seconds, preferably 24 to 36 seconds, more preferably 28 to 32 seconds, and more preferably 30 seconds.

[0055] In the present invention, the stirring time in step (3) is 4 to 6 minutes, preferably 5 minutes.

[0056] In the present invention, the cement used is low-alkalinity sulphoaluminate cement produced by Jiuqi Building Materials, with an alkalinity value of 9.6; codfish antifreeze protein is selected from deep-sea codfish and purchased from Shanghai Naijin Industrial Co., Ltd.; coarse / fine aggregates are purchased from Xiamen Aceo Standard Sand Co., Ltd.

[0057] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0058] Example 1

[0059] A high-freeze-resistant biomass concrete for extreme freeze-thaw environments, the preparation method of which is as follows: 0.2 parts of cod antifreeze protein are added to water in small amounts for multiple times (the proportion of each addition does not exceed 0.5% of the total mass to ensure uniform dispersion of the antifreeze protein during dissolution to avoid precipitation and aggregation), magnetic stirring for 12 minutes to obtain a uniformly dispersed mixed solution of cod antifreeze protein and water for concrete mixing; 10 parts of low-alkalinity sulphoaluminate cement and the mixed solution are added and stirred for 30 seconds to obtain cement paste, wherein the mass ratio of cement to water is 1:0.45; 30 parts of fine aggregate (machine-made sand) with a particle size of 5 mm are added and stirred for 5 minutes; finally, the stirred mixture is molded, vibrated, formed and cured to obtain the high-freeze-resistant biomass concrete.

[0060] Example 2

[0061] A high-freeze-resistant biomass concrete for extreme freeze-thaw environments, the preparation method of which is as follows: 0.4 parts of cod antifreeze protein are added to water in small amounts for multiple times (the proportion of each addition does not exceed 0.5% of the total mass to ensure uniform dispersion of the antifreeze protein during dissolution to avoid precipitation and aggregation), magnetic stirring for 12 minutes to obtain a uniformly dispersed mixed solution of cod antifreeze protein and water for concrete mixing; 12 parts of low-alkalinity sulphoaluminate cement and the mixed solution are added and stirred for 30 seconds to obtain cement paste, wherein the mass ratio of cement to water is 1:0.45; 30 parts of fine aggregate (natural sand) with a particle size of 4 mm are added and stirred for 5 minutes; finally, the stirred mixture is molded, vibrated, formed and cured to obtain the high-freeze-resistant biomass concrete.

[0062] Comparative Example 1

[0063] The method of Example 1 was followed, except that no cod antifreeze protein was added.

[0064] Comparative Example 2

[0065] The method of Example 2 was followed, except that no cod antifreeze protein was added.

[0066] Experimental Example 1

[0067] 1. Freeze-thaw cycle test: The concrete mixed in each embodiment and comparative example was made into a test piece of 40 mm×40 mm×160 mm, and the curing age was 14 days. After the test piece was saturated with water, each test piece was subjected to 60 freeze-thaw treatments according to the quick freezing method of GB / T 50082-2009 "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete", and the mass loss rate of each test piece was tested every 10 freeze-thaw cycles.

[0068] 2. Hole solution freezing temperature test:

[0069] ① The concrete mixed in each embodiment and comparative example was used to prepare the pore solution according to the following steps:

[0070] i) 200 g of the mixed concrete is placed in a centrifuge tube, and the centrifuge tube is placed symmetrically in a centrifuge;

[0071] ii) Set the centrifuge speed to 4000r / min and the time to 5min;

[0072] iii) Take the supernatant and pipette it into a glass bottle to obtain the well solution.

[0073] ② Use differential scanning calorimeter to test the freezing temperature:

[0074] i) Add no more than 40 mg of the pore solution into a small crucible and seal it, and record the tare weight and total weight;

[0075] ii) Place the crucible in the instrument and input the recorded weight into the software, while placing an empty crucible as a reference;

[0076] iii) setting the temperature range of the differential scanning calorimeter to -40°C to 20°C, the cooling rate to 10°C / min, and the heating rate to 2.5°C / min;

[0077] IV) The reference object and the sample are placed in the same temperature environment through a program controller. The relationship curve between the heat difference and temperature between the sample and the reference object is the DSC curve, and the freezing temperature is determined by the temperature transition value.

[0078] 3. Ice crystal morphology test

[0079] The solution prepared in the hole solution freezing test was taken, and the ice crystal morphology was observed using the device provided by CN201615966U.

[0080] The results are as follows Figure 3 to Figure 9 As shown: Combining the performance test results of Example 1, Comparative Example 1 and Example 2, Comparative Example 2, it can be seen that the presence of biomass materials significantly increases the freeze-thaw cycle number of cement mortar specimens from 30 times to more than 60 times, and the antifreeze effect is improved by more than 50%; the polar side chains of the biomass materials are adsorbed to the surface of ice crystals through hydrogen bonds, while the non-polar side chains are still exposed, resulting in the formation of submicroscopic curved surfaces of ice crystals, resulting in an increase in the surface free energy of ice crystals, preventing other water molecules from further mixing with ice crystals, and reducing the freezing temperature of the pore solution; the ice crystal morphology of the pore solution changes from the original cone to feather, and the ice crystals become smaller as the amount of antifreeze protein increases, showing a very soft tissue on a macro scale, and the frost heave stress is significantly reduced, thereby improving the frost resistance of the concrete (the ice crystal diagram in Comparative Example 2 is omitted here, and there is no obvious difference between the ice crystal diagram in Comparative Example 2 and the ice crystal diagram in Comparative Example 1).

[0081] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. Application of cod antifreeze protein in the preparation of high frost-resistant concrete.

2. A highly frost-resistant biomass concrete, characterized in that: The invention comprises the following components in parts by weight: 0.1 to 0.5 parts of cod antifreeze protein, 8 to 16 parts of cement and 25 to 35 parts of aggregate.

3. The high frost resistance biomass concrete according to claim 2, characterized in that: The cement is low-alkalinity sulphoaluminate cement.

4. The high frost resistance biomass concrete according to claim 2, characterized in that: The aggregate is coarse aggregate and / or fine aggregate.

5. The high frost resistance biomass concrete according to claim 4, characterized in that: The particle size of the coarse aggregate is 6 to 20 mm; the particle size of the fine aggregate is 2 to 5 mm.

6. A highly frost-resistant biomass concrete according to claim 2 or 4, characterized in that: The aggregate is one or more of natural crushed stone, pebbles, machine-made sand or natural sand.

7. The method for preparing a highly frost-resistant biomass concrete according to any one of claims 2 to 6, characterized in that: The steps include: (1) mixing cod antifreeze protein with water to obtain concrete mixing water; (2) mixing the concrete mixing water and cement to obtain cement paste; (3) The cement paste is mixed with aggregate to obtain high frost resistance biomass concrete.

8. The method for preparing a highly frost-resistant biomass concrete according to claim 7, characterized in that: The mass ratio of cement to water is 1:0.3-0.

6.

9. The method for preparing a highly frost-resistant biomass concrete according to claim 7, characterized in that: The method also includes the steps of molding, vibrating, shaping and curing the high frost-resistant biomass concrete.

10. The method for preparing a highly frost-resistant biomass concrete according to claim 7, characterized in that: The stirring time in step (1) is 8 to 16 minutes; the stirring time in step (2) is 20 to 40 seconds; and the stirring time in step (3) is 4 to 6 minutes.

Citation Information

Patent Citations

  • A cooled stage for an optical microscope

    CN201615966U